Pengaruh Krisis Moneter Pada Efisiensi Perusahaan Publik Di Bursa Efek Jakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT The monetery crisis has attacted Indonesia since the mid of 1997. Sharp increase of US dollar exchange rate and the due of international loan hurled Indonesian economy and business painfully. It is very rational that this national problem influence the performance of companies listed in Jakarta Stock Exchange (JSX). Increasing the price, in rupiah, of imported material and other goods and services from other countries that based on dollar value destorted the ability of companies to maintain their financial performance. This study intent to identibr and analyze the impact of monetary crisis to the performance of companies listed in JSX. 129 manufacturing companies selected as sample to answer the question whether the monetary crisis has already attacted the performance of companies listed in JSX. The sample, then, sub-grouped to the four sub-sample based on sector of businesses to explain which of the sector hurting most. By using t-test and spearman rank correlation all the hypothesis are tested. Six financial ratios used to represent the company performance. Those ratios are consist of three ratio categories: profitability, liquidity and operation, and leverage. The results of the study shown that companies listed in JSX are impacted by monetary crisis. All means of financial ratios after crisis used in this study are worse than those in the year before crisis. 9-test results show that all indicators of ratios significantly different except Current Ratio and Debt to Equity Ratio. The explanation that can be provided from these findings is that the impact of crisis to those two ratios cannot be shown in the very short time (only six months), because the liquidity, debt, and equity of the sample are still not significantly changing from the first semester of the year of 1997. The explanation of those finding also supported by analysis of sectors of industry. Four sectors, taken from JSX directory, shown consistently with total sample except sector of heavy investment as: building construction, real estate, and other heavy investment industries. The explanation of this exception is that those companies in sector 4 have not yet been impacted by the crisis.